Zeolite modified hydraulic lime-based material and application thereof

By introducing synthetic zeolites and protective agents into hydraulic lime, zeolite-modified hydraulic lime-based materials are prepared, which solves the problems of slow curing time, insufficient early strength and poor durability in the reinforcement and protection of rock-steel cultural relics, and achieves efficient reinforcement and protection of rock-steel cultural relics.

CN119735415APending Publication Date: 2025-04-01FUDAN UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411888103.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing hydraulic lime has the disadvantages of slow curing time, insufficient early strength, and poor durability in the reinforcement and protection of rock and soil cultural relics, and further modification and optimization are needed.

Method used

The zeolite-modified hydraulic lime-based material is used, and the components include synthetic zeolites and natural hydraulic lime. The synthetic zeolite accounts for 8 to 30% by weight of the total mass. Protective agents and functional additives are introduced into the material. The slurry after compounding has the characteristics of controllability, controllable curing time, light weight, low soluble salt content and high early strength.

Benefits of technology

It has achieved efficient reinforcement and protection of damaged rock bodies of rock mass in geotechnical cultural relics, with high applicability, safety and weather resistance, and significantly improved the early strength and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735415A_ABST
    Figure CN119735415A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials and cultural relic protection, and particularly relates to a zeolite modified hydraulic lime-based material and application thereof. The zeolite modified hydraulic lime-based material provided by the invention comprises the following components: synthetic zeolite and natural hydraulic lime, wherein the synthetic zeolite accounts for 8-30wt% of the total mass of the synthetic zeolite and the natural hydraulic lime. The zeolite modified hydraulic lime-based material provided by the invention comprises natural hydraulic lime and zeolite dispersed in the hydraulic lime, and slurry obtained by compounding the material and water has the characteristics of controllable fluidity, controllable curing time, light weight, low soluble salt content, high early strength and the like. In addition, the introduction of the protective agent and / or the functional additive can further improve the performance of the material in a targeted manner. The zeolite modified hydraulic lime-based material provided by the invention has relatively high applicability, safety and weather resistance for reinforcing and protecting rock soil cultural relics which are subjected to weathering damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials and cultural relics protection, and in particular relates to a zeolite-modified hydraulic lime-based material and application thereof. Background Art

[0002] During the preservation process, rock and soil cultural relics, mainly grotto temples, murals, and mausoleum sites, have been affected by geological conditions and natural environment for a long time, resulting in varying degrees of weathering damage to the rock mass (such as cracking, falling blocks, and even collapse), which seriously damages the integrity and continuity of precious rock and soil cultural relics. Therefore, the design and development of high-performance reinforcement and protection materials has always been the research focus in the field of rock and soil cultural relics protection.

[0003] As a traditional silicate building material, hydraulic lime has attracted widespread attention and favor from cultural relics restoration workers in recent years. It has both air-hardening components (calcium hydroxide) and hydraulic components (dicalcium silicate), and has the advantages of low soluble salt content, good compatibility, low shrinkage and moderate strength. Compared with cement and traditional mortar, hydraulic lime has played an irreplaceable advantage in the reinforcement and protection of rock and soil cultural relics. However, in actual applications, hydraulic lime still has shortcomings such as slow curing time, insufficient early strength and poor durability, which require further modification and optimization. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a zeolite-modified hydraulic lime-based material and its application. The zeolite-modified hydraulic lime-based material provided by the present invention has a good use effect in the reinforcement and protection of damaged rock and soil cultural relics.

[0005] The invention provides a zeolite-modified hydraulic lime-based material, which comprises synthetic zeolite and natural hydraulic lime, wherein the synthetic zeolite accounts for 8-30wt% of the total mass of the synthetic zeolite and the natural hydraulic lime.

[0006] Preferably, the synthetic zeolite is Y-type zeolite.

[0007] Preferably, the Y-type zeolite has a particle size of 1 to 3 μm and a specific surface area of ​​600 to 1000 m 2 / g.

[0008] Preferably, the natural hydraulic lime is one or more of NHL2, NHL3.5 and NHL5.

[0009] Preferably, the particle size of the natural hydraulic lime is less than 30 μm.

[0010] Preferably, the components also include a protective agent, which is one or more of Ag nitrate, Ag chloride, Ag oxide, Ag hydroxide, Ag carbonate, Zn nitrate, Zn chloride, Zn oxide, Zn hydroxide, Zn carbonate, Si nitrate, Si chloride, Si oxide, Si hydroxide, Si carbonate, Ca nitrate, Ca chloride, Ca oxide, Ca hydroxide and Ca carbonate.

[0011] Preferably, the components further include functional additives, and the functional additives are one or more of antifreeze agents, water reducers and quick-setting agents.

[0012] The invention provides a zeolite-modified hydraulic lime-based grouting material, the components of which include the zeolite-modified hydraulic lime-based material described in the above technical solution and water.

[0013] Preferably, the mass ratio of the zeolite-modified hydraulic lime-based material to water is 100:(40-150).

[0014] The present invention provides a method for reinforcing a damaged rock mass of a rock and soil cultural relic, comprising the following steps:

[0015] The damaged rock mass of rock and soil cultural relics is reinforced by using the zeolite-modified hydraulic lime-based grouting material described in the above technical solution.

[0016] Compared with the prior art, the present invention provides a zeolite-modified hydraulic lime-based material and its application. The components of the zeolite-modified hydraulic lime-based material provided by the present invention include synthetic zeolite and natural hydraulic lime, and the synthetic zeolite accounts for 8 to 30wt% of the total mass of the synthetic zeolite and the natural hydraulic lime. The zeolite-modified hydraulic lime-based material provided by the present invention includes natural hydraulic lime and zeolite dispersed in hydraulic lime. The slurry after compounding the material with water has the characteristics of controllable fluidity, controllable curing time, light weight, low soluble salt content and high early strength. In addition, the introduction of protective agents and / or functional additives can further improve the performance of the material in a targeted manner. The zeolite-modified hydraulic lime-based material provided by the present invention has high applicability, safety and weather resistance for the reinforcement and protection of rock and soil cultural relics that have been weathered and damaged. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0018] Figure 1 is a SEM image of the zeolite provided in the embodiment of the present invention;

[0019] Figure 2 This is a SEM picture of the zeolite-modified hydraulic lime-based grouting material provided in an embodiment of the present invention after curing and solidification. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The invention provides a zeolite-modified hydraulic lime-based material, which comprises synthetic zeolite and natural hydraulic lime.

[0022] In the zeolite-modified hydraulic lime-based material provided by the present invention, the natural hydraulic lime is preferably one or more of NHL2, NHL3.5 and NHL5; and the particle size of the natural hydraulic lime is preferably <30 μm.

[0023] In the zeolite-modified hydraulic lime-based material provided by the present invention, the synthetic zeolite is preferably Y-type zeolite; the particle size of the Y-type zeolite is preferably 1 to 3 μm; the specific surface area of ​​the Y-type zeolite is preferably 600 to 1000 m 2 / g.

[0024] In the zeolite-modified hydraulic lime-based material provided by the present invention, the synthetic zeolite accounts for 8 to 30 wt% of the total mass of the synthetic zeolite and the natural hydraulic lime, specifically 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt% or 30 wt%.

[0025] In the zeolite-modified hydraulic lime-based material provided by the present invention, the components preferably also include a protective agent; the protective agent is preferably one or more of Ag nitrate, Ag chloride, Ag oxide, Ag hydroxide, Ag carbonate, Zn nitrate, Zn chloride, Zn oxide, Zn hydroxide, Zn carbonate, Si nitrate, Si chloride, Si oxide, Si hydroxide, Si carbonate, Ca nitrate, Ca chloride, Ca oxide, Ca hydroxide and Ca carbonate, more preferably one or more of AgNO3, ZnCl2, SiO2, Ca(OH)2, CaCO3 and CaCl2; the protective agent is preferably loaded on the surface of the synthetic zeolite.

[0026] In the zeolite-modified hydraulic lime-based material provided by the present invention, the specific process of loading the protective agent on the surface of the synthetic zeolite preferably includes: dispersing the synthetic zeolite into the protective agent aqueous solution, heating and mixing for a period of time, and then performing solid-liquid separation to obtain a synthetic zeolite with a protective agent loaded on the surface. Wherein, the concentration of the protective agent aqueous solution is preferably 0.05-1wt%, specifically 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%; the mass ratio of the protective agent aqueous solution to the synthetic zeolite (i.e., liquid-to-solid ratio) is preferably (50-150):1 , specifically 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1 or 150:1; the heating and mixing temperature is preferably 50-80°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C; the heating and mixing time is preferably 1-5h, specifically 1h, 2h, 3h, 4h or 5h.

[0027] In the zeolite-modified hydraulic lime-based material provided by the present invention, the components preferably further include functional additives; the functional additives are preferably one or more of antifreeze agents, water reducers and quick-setting agents.

[0028] In the zeolite-modified hydraulic lime-based material provided by the present invention, the content of the functional additive in the zeolite-modified hydraulic lime-based material is preferably 0.05-0.5wt%, specifically 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%.

[0029] The present invention has no particular limitation on the preparation method of the zeolite-modified hydraulic lime-based material, and the raw materials can be uniformly mixed according to the composition ratio. If the components contain a protective agent, it is preferred to first load the protective agent on the surface of the synthetic zeolite, and then uniformly mix the surface-loaded synthetic zeolite with the remaining raw materials.

[0030] The present invention also provides a zeolite-modified hydraulic lime-based grouting material, the composition of which includes the zeolite-modified hydraulic lime-based material described in the above technical solution and water. The mass ratio of the attapulgite-modified hydraulic lime-based material to water is preferably 100:(40-150), specifically 100:40, 100:50, 100:60, 100:70, 100:80, 100:90, 100:100, 100:110, 100:120, 100:130, 100:140 or 100:150.

[0031] The present invention has no particular limitation on the preparation method of the zeolite-modified hydraulic lime-based grouting material, and the raw materials can be uniformly mixed according to the component ratio.

[0032] The present invention also provides a method for reinforcing a damaged rock mass of a rock and soil cultural relic, comprising the following steps:

[0033] The damaged rock mass of rock and soil cultural relics is reinforced by using the zeolite-modified hydraulic lime-based grouting material described in the above technical solution.

[0034] The technical solution provided by the present invention has a good use effect in the reinforcement and protection of damaged rock and soil cultural relics. More specifically, it has at least the following advantages:

[0035] (1) The zeolite-modified hydraulic lime-based material of the present invention is mainly composed of synthetic zeolite and hydraulic lime. Synthetic zeolite, as a type of porous silicate, has a large specific surface area and high reactivity, and can greatly improve the internal density and mechanical strength of the material through volcanic ash reaction. At the same time, synthetic zeolite can effectively load (ion exchange or adsorption) other protective agents and functional additives to achieve multifunctional reinforcement protection of the material.

[0036] (2) The preparation process of the zeolite-modified hydraulic lime-based material of the present invention is simple and has a prospect for large-scale application. The slurry after compounding with water has the characteristics of light weight, low soluble salt content, short curing time, low shrinkage and expansion, and shows good rock compatibility, and is suitable for the reinforcement and protection of rock and soil cultural relics.

[0037] (3) The slurry of the zeolite-modified hydraulic lime-based material and water is used to reinforce and protect the weathered and damaged rock and soil cultural relics, and the protective effect is remarkable. The material exhibits suitable bonding strength and good durability, and can achieve long-term reinforcement and safe protection of the damaged rock mass of rock and soil cultural relics.

[0038] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.

[0039] In the following examples and comparative examples, the particle size of natural hydraulic lime (NHL5) is less than 30 μm and is purchased from Shanghai Desaibao Building Materials Co., Ltd.; the particle size of synthetic zeolite (type Y) is 1 to 3 μm and the specific surface area is 600 to 1000 m 2 / g, purchased from Tianjin Nankai University Catalyst Factory, microscopic morphology Figure 1 As shown; silver nitrate and zinc chloride were purchased from McLean Biological Co., Ltd.; nano calcium hydroxide and nano silicon dioxide were purchased from Hebei Nanometal Technology Co., Ltd.; water reducer was purchased from Guangzhou Zhongwan New Materials Co., Ltd.; antifreeze was purchased from Beijing Mengtai Building Materials Weiye.

[0040] Example 1

[0041] With AgNO3 as a protective agent, a 0.05wt% AgNO3 solution is prepared, and then synthetic zeolite (type Y) is uniformly dispersed in the AgNO3 solution with a liquid-solid ratio of 100:1; stirring at 65°C for 3 hours for surface loading, centrifugal separation, to obtain synthetic zeolite with surface loading of protective agent; the synthetic zeolite with surface loading of protective agent and natural hydraulic lime (NHL5) are dry-mixed evenly, wherein the mass ratio of hydraulic lime to synthetic zeolite (excluding the loaded protective agent) is 5:1; the dry-mixed mixture is evenly mixed with water at a mass ratio of 1:0.6, and after stirring with a mortar mixer, a zeolite-modified hydraulic lime-based slurry for reinforcement and protection of damaged rock masses of rock and soil cultural relics is obtained.

[0042] The slurry prepared in this embodiment has controllable curing time, high early strength, uniaxial compressive strength of up to 10 MPa after 7 days of curing, and bonding strength of 3.26 MPa after 28 days of curing. It has good impermeability and durability. The microscopic morphology after 28 days of curing is as follows: Figure 2 Moreover, the slurry loaded with AgNO3 protective agent has certain antibacterial properties and can effectively resist microbial erosion in the reinforced parts.

[0043] Example 2

[0044] With ZnCl2 as a protective agent, a 0.2wt% ZnCl2 solution is prepared, and then synthetic zeolite (type Y) is uniformly dispersed in the ZnCl2 solution with a liquid-to-solid ratio of 100:1; stirring at 65°C for 3 hours for surface loading, centrifugal separation, and obtaining synthetic zeolite with a surface loaded with a protective agent; dry-mixing the synthetic zeolite with a surface loaded with a protective agent with natural hydraulic lime (NHL5), wherein the mass ratio of hydraulic lime to synthetic zeolite (excluding the loaded protective agent) is 10:1; the dry-mixed mixture is uniformly mixed with water at a mass ratio of 1:0.6, and after stirring with a mortar mixer, a zeolite-modified hydraulic lime-based slurry for reinforcing and protecting damaged rock masses of rock and soil cultural relics is obtained.

[0045] The slurry prepared in this embodiment has a uniaxial compressive strength of 6.25 MPa after curing for 7 days, and a bonding strength of 2.32 MPa after curing for 28 days. In addition, the slurry loaded with ZnCl2 protective agent has certain antibacterial and anti-ultraviolet properties.

[0046] Example 3

[0047] Ca(OH)2 (particle size 50nm) is used as a protective agent, a 1wt% Ca(OH)2 solution is prepared, and then synthetic zeolite (type Y) is uniformly dispersed in the Ca(OH)2 solution with a liquid-to-solid ratio of 100:1; stirring is performed at 65°C for 3 hours for surface loading, and centrifugal separation is performed to obtain synthetic zeolite with a surface loaded with a protective agent; the synthetic zeolite with a surface loaded with a protective agent is dry-mixed with natural hydraulic lime (NHL5), wherein the mass ratio of hydraulic lime to synthetic zeolite (excluding the loaded protective agent) is 5:1; the dry-mixed mixture is uniformly mixed with water at a mass ratio of 1:0.6, and after stirring with a mortar mixer, a zeolite-modified hydraulic lime-based slurry for reinforcing and protecting damaged rock masses of rock and soil cultural relics is obtained.

[0048] After 28 days of curing, the wave velocity of the solidified sample in ultrasonic testing can reach 2.24 km / s, the porosity is 45.63%, and the permeability is 0.23×10 -8 cm / s, the 28-day compressive strength is 18.32MPa, and the 28-day bonding strength is 3.67MPa, which has good salt crystallization resistance.

[0049] Example 4

[0050] The natural hydraulic lime (NHL5) and the synthetic zeolite (type Y) are mixed evenly at a mass ratio of 5:1, and then 0.2% of the total weight of a polycarboxylic acid water reducer (maleic anhydride as the main chain and polyethers with different side chain lengths grafted thereon) is added and mixed evenly; the evenly mixed materials are mixed evenly with water at a mass ratio of 1:0.6, and after stirring with a mortar mixer, a zeolite-modified hydraulic lime-based slurry for reinforcement and protection of damaged rock masses of rock and soil cultural relics is obtained.

[0051] The slurry prepared in this embodiment has a fluidity of up to 236.4 mm (Method for Determining Fluidity of Cement Mortar (GB / T2419-2016)), a viscosity of 0.16 Pa·s at 25°C, and a density of 2.87 g / cm after curing for 28 days. 3 The early 7-day folding strength is 4.25MPa, and the 28-day bonding strength is 3.16MPa.

[0052] Example 5

[0053] The natural hydraulic lime (NHL5) and the synthetic zeolite (type Y) are mixed evenly at a mass ratio of 5:1, and then 0.3% of the total weight of the antifreeze agent (polyacrylate) is added and mixed evenly; the evenly mixed materials are mixed evenly with water at a mass ratio of 1:0.6, and after stirring with a mortar mixer, a zeolite-modified hydraulic lime-based slurry for reinforcement and protection of damaged rock masses of rock and soil cultural relics is obtained.

[0054] After the slurry prepared in this embodiment was cured for 28 days, the wave velocity of the cured sample for ultrasonic testing could reach 2.32 km / s, and the porosity was 44.6%; the mass loss rate of the cured sample was less than 3% during 20 freeze-thaw cycles under low temperature of -30°C and high temperature of 30°C, and no obvious cracks appeared on the surface of the sample.

[0055] Example 6

[0056] In this embodiment, the protective agent is nano-SiO2 (particle size 20-100 nm), which is used to enhance the volcanic ash reaction and strengthen the cementation of the slurry. The rest is the same as in Example 3.

[0057] After 28 days of curing, the wave velocity of the solidified sample in ultrasonic testing can reach 2.48 km / s, the porosity is 43.6%, and the permeability is 0.21×10 -8 cm / s, uniaxial compressive strength is 19.4MPa, and bonding strength is 3.79MPa.

[0058] Example 7

[0059] In this embodiment, the protective agent is CaCO3 nano whiskers (diameter is 50-100nm, aspect ratio is 20-200:1), which can effectively improve the mechanical properties of the slurry and enhance the cementation effect. The rest is the same as in Example 3.

[0060] After 28 days of curing, the wave velocity of the ultrasonic test of the solidified sample can reach 2.35 km / s, the porosity is 44.8%, and the permeability is 0.22×10 -8 cm / s, uniaxial compressive strength is 19.8MPa, and bonding strength is 4.02MPa.

[0061] Example 8

[0062] In this embodiment, the protective agent is CaCl2, which is used to accelerate the hydration reaction of hydraulic petrochemicals and improve the density and mechanical strength of the hardened specimens. The rest is the same as in Example 3.

[0063] After 28 days of curing, the wave velocity of the ultrasonic test of the solidified sample can reach 2.18 km / s, the porosity is 46.6%, and the permeability is 0.26×10 -8 cm / s, uniaxial compressive strength is 17.5MPa, and bonding strength is 3.4MPa.

[0064] Example 9

[0065] In this embodiment, the raw material mass ratio is as follows: synthetic zeolite is 15%, hydraulic lime is 84.9%, polycarboxylate water reducer is 0.1%, and the rest is the same as in Embodiment 4.

[0066] The slurry prepared in this embodiment has a fluidity of up to 236.4 mm and a viscosity of 0.18 Pa·s at 25°C. After curing for 28 days, the density of the cured sample can reach 2.87 g / cm 3 , the uniaxial compressive strength is 15.8MPa and the bonding strength is 2.68MPa.

[0067] Example 10

[0068] In this embodiment, the mass ratio of the mixture of hydraulic lime, synthetic zeolite and antifreeze agent to water is 1:0.7, and the rest is the same as in Embodiment 5.

[0069] After the slurry prepared in this embodiment is cured for 28 days, the wave velocity of the cured sample for ultrasonic testing can reach 2.32 km / s, and the porosity is 44.6%; the mass loss rate of the cured specimen after 20 freeze-thaw cycles under low temperature of -30°C and high temperature of 30°C is less than 3%.

[0070] Comparative Example 1

[0071] In this embodiment, natural zeolite (with a particle size of 2 to 10 μm) is used instead of synthetic zeolite, and the rest is the same as in Embodiment 1.

[0072] After curing, the natural zeolite-modified hydraulic lime material sets slowly, has low early strength, and its performance development does not meet the needs of reinforcement and protection of rock and soil cultural relics.

[0073] After 28 days of curing, the wave velocity of the ultrasonic test sample can reach 1.75 km / s, the porosity is 49.6%, and the permeability is 0.31×10 -8 cm / s, uniaxial compressive strength is 10.6MPa, and bonding strength is 2.2MPa.

[0074] Comparative Example 2

[0075] In this embodiment, the water reducing agent is omitted, and the rest is the same as in Embodiment 4.

[0076] Due to the lack of water reducing agent, the fluidity of the material decreases. In the application scenario of rock and soil cultural relics reinforcement and protection, the slurry with low fluidity is not conducive to bonding and is prone to cracks on the surface during the curing process.

[0077] The slurry prepared in this embodiment has a fluidity of up to 213.7 mm and a viscosity of 0.19 Pa·s at 25°C. After curing for 28 days, the density of the cured sample can reach 2.75 g / cm 3 .

[0078] Comparative Example 3

[0079] In this embodiment, the antifreeze agent is omitted, and the rest is the same as in Embodiment 5.

[0080] Due to the lack of antifreeze agent, the hardened specimens showed minor damage on the edges after 20 freeze-thaw cycles at low temperature of -30°C and high temperature of 30°C, and the mass loss rate was less than 3%, indicating that its freeze-thaw resistance decreased slightly.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A zeolite-modified hydraulic lime-based material, characterized in that: The composition comprises synthetic zeolite and natural hydraulic lime, wherein the synthetic zeolite accounts for 8-30wt% of the total mass of the synthetic zeolite and the natural hydraulic lime.

2. The zeolite-modified hydraulic lime-based material according to claim 1, characterized in that: The synthetic zeolite is Y-type zeolite.

3. The zeolite-modified hydraulic lime-based material according to claim 2, characterized in that: The particle size of the Y-type zeolite is 1 to 3 μm, and the specific surface area is 600 to 1000 m 2 / g.

4. The zeolite-modified hydraulic lime-based material according to claim 1, characterized in that: The natural hydraulic lime is one or more of NHL2, NHL3.5 and NHL5.

5. The zeolite-modified hydraulic lime-based material according to claim 4, characterized in that: The particle size of the natural hydraulic lime is less than 30 μm.

6. The zeolite-modified hydraulic lime-based material according to claim 1, characterized in that: The components also include a protective agent, which is one or more of Ag nitrate, Ag chloride, Ag oxide, Ag hydroxide, Ag carbonate, Zn nitrate, Zn chloride, Zn oxide, Zn hydroxide, Zn carbonate, Si nitrate, Si chloride, Si oxide, Si hydroxide, Si carbonate, Ca nitrate, Ca chloride, Ca oxide, Ca hydroxide and Ca carbonate.

7. The zeolite-modified hydraulic lime-based material according to claim 1, characterized in that: The composition further comprises a functional additive, wherein the functional additive is one or more of an antifreeze agent, a water reducing agent and an accelerating setting agent.

8. A zeolite-modified hydraulic lime-based grouting material, characterized in that: The composition comprises the zeolite-modified hydraulic lime-based material according to any one of claims 1 to 7 and water.

9. The zeolite-modified hydraulic lime-based grouting material according to claim 8, characterized in that: The mass ratio of the zeolite-modified hydraulic lime-based material to water is 100:(40-150).

10. A method for reinforcing a damaged rock mass of a rock and soil cultural relic, characterized in that: The following steps are involved: The damaged rock mass of rock and soil cultural relics is reinforced by using the zeolite-modified hydraulic lime-based grouting material described in claim 8 or 9.

Citation Information

Patent Citations

  • Infusion and binding material composition

    CN101811853A

  • Slow-release zeolite molecular sieve integrated protective agent and preparation method and application thereof

    CN110205864A